Painted Discourses: Lived Experience in the Nasca Visual System - (:unkn) unknown (My University, 2013)
This paper looks at the ancient Peruvian culture of the Nasca and discusses the ceramic iconography in terms of lived experience. By understanding the images as "discourse," a term from the philosopher Michel Foucault, scholars can begin to contextualize the iconography not simply as bearers of esoteric meaning, but sociopolitical statements regarding how the ancient peoples experienced their world.
Keywords: Cahuachi; Discourse; Nasca